Symposium 8: Changing Belief Systems: The Effect of Staff Attitudes on Innovation and Sustainability - Bricheno, Patricia; Higgison, Carol (Proceedings of the International Conference on Networked Learning, 2004)
Previous studies of UK Further and Higher education have highlighted the growing importance of networked learning (JISC, 2002). However, little research has been carried out into the management of large-scale networked learning. This paper looks at the relationship between the formal strategies put in place to enable the implementation and sustainability of large-scale Networked Learning and the attitudes of staff. It identifies different organisational design issues and the impact they have had on practice. The organisational foci which inform this study include: the importance of how strategy is developed (Gibbs, 1999); staff development and support (Hart, Ryan and Bagdon, 2000); commitment at the institutional level (McCartan, Lewins, and Hodgson, 2000); and personal issues such as motivation (e.g. Banks and Powell, 2002; Bothams and Fordyce, 2002). Since research has suggested that differences between institutions leads to characteristically different strategies (Gibbs, 1999) this study uses a multiple case study approach, each case is an educational organization, and the cases are selected to represent different types of educational institutions; the types being established by prior hypothesizing (Yin, 2003). Each case study uses data from three main sources: questionnaires, institutional documents, and semi-structured interviews. This data is used to illustrate and discuss relationships between staff attitudes and the types of organisational climate and support structures within institutions. The findings are used to identify important issues and draw out key themes to support sustainable innovation. An in-depth qualitative investigation has been used to develop a full understanding of complex underlying issues involved in the responses of people to institutional change towards large-scale networked learning.